The impact of nutrition and feeding time on the regulation of gene expression in the central circadian clock of Drsosophila Melanogaster - Diab, Arwa (AUC Knowledge Fountain, 2014)
The circadian clock plays an essential role in most organisms by allowing their adaptation to the daily environmental changes mainly light/dark cycles and also temperature. Circadian rhythms persist in constant conditions indicating an auto regulatory molecular circadian clock. Here, we investigated the possibility that the circadian clock of Drosophila can also be entrained by scheduled feeding. Cycles of 12 hours feeding and 12 hours starvation could entrain the molecular circadian oscillation in key pacemaker neurons of Drosophila. Clock proteins CLOCK (CLK) and PERIOD (PER) showed a 24 hour oscillation in the small and large ventral lateral neurons after entrainment by scheduled feeding of a balanced diet, carbohydrate-only diet, as well as protein only diet. Lipid diet did not prove its effectiveness in the clock's entrainment. The neuropeptide Pigment Dispersing Factor (PDF) plays an important role in entrainment of the circadian clock by light-dark cycles, but it appears to be not essential for entrainment of the circadian clock in response to cyclic feeding. Scheduled feeding resulted in 24 hour oscillations of CLK and PER in small and large ventral lateral neurons of pigment dispersing factor mutant flies (pdf01). Time of feeding appears to be a strong entrainment cue for the circadian clock as it affected the phase of amplitude of molecular oscillations even in light dark cycles. These results establish an entrainment of the Drosophila circadian clock by scheduled feeding, indicating a regulation of the circadian oscillator by metabolism in Drosophila.